PENGARUH SOCIAL MEDIA MARKETING TERHADAP PENINGKATAN KUNJUNGAN DI LAYANAN KESEHATAN - Shantika, Widya Ayu; Merdayana, Merdayana; Kusumasari, Meyta Minggar; Fitriany, Shafira; Drehem, Shaleh Muhammad; Al Azim, Muhammad Rifqi; Rohendi, Acep (JURNAL EKONOMI BISNIS DAN MANAJEMEN (EKO-BISMA), 2026)
ABSTRACT The digital transformation has reshaped the hospital marketing landscape, making digital marketing an imperative strategic instrument. This study aims to analyze the influence of digital marketing strategies, particularly social media marketing (SMM), on increasing patient visits in hospitals through a systematic literature review of 14 recent empirical studies (2018-2025). The findings reveal that the impact of SMM on patient visits is indirect and complex, mediated by increased brand awareness, electronic word of mouth (e-WOM), relationship quality, and patient experience. The post-pandemic context serves as a significant catalyst accelerating the adoption of these strategies. The effectiveness of SMM heavily depends on selecting the right platforms (such as Instagram and TikTok), creating educational and interactive content, and synergistic integration with the conventional marketing mix (7P) and Integrated Marketing Communication (IMC) framework. However, the success of this strategy remains grounded in core service quality and requires attention to ethical challenges and continuous evaluation. In conclusion, SMM functions as a catalyst for digital transformation that builds intangible assets, which are then converted into physical visits, thereby significantly contributing to hospital sustainability in the competitive era. Keywords: Digital Marketing, Social Media, Patient Visits, Conventional Marketing Mix, Integrated Marketing Communication